Anhydrous phosphoric acid functionalized sintered mesoporous silica nanocomposite proton exchange membranes for fuel cells - Zeng, J.; He, B.; Lamb, K.; De Marco, Roland; Shen, P.; Jiang, San Ping (American Chemical Society, 2013)
A novel inorganic proton exchange membrane based on phosphoric acid (PA)-functionalized sintered mesoporous silica, PA-meso-silica, has been developed and investigated. After sintering at 650 °C, the meso-silica powder forms a dense membrane with a robust and ordered mesoporous structure, which is critical for retention of PA and water within the porous material. The PA-meso-silica membrane achieved a high proton conductivity of 5 × 10–3 to 5 × 10–2 S cm–1 in a temperature range of 80–220 °C, which is between 1 and 2 orders of magnitudes higher than a typical membrane Nafion 117 or polybenzimidazole (PBI)/PA in the absence of external humidification. Furthermore, the PA-meso-silica membranes exhibited good chemical stability along with high performance at elevated temperatures, producing a peak power density of 632 mW cm–2 using a H2 fuel at 190 °C in the absence of external humidification. The high membrane proton conductivity and excellent fuel cell performance demonstrate the utility of PA-meso-silica as a new class of inorganic proton exchange membranes for use in the high-temperature proton exchange membrane fuel cells (PEMFCs).